2022
DOI: 10.1021/acsami.2c18893
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Ligament-Mimetic Fibrous Scaffolds Regulate YAP-Associated Fibroblast Behaviors and Promote Regeneration of Periodontal Defect in Relation to the Scaffold Topography

Abstract: Although multiple regenerative strategies are being developed for periodontal reconstruction, guided periodontal ligament (PDL) regeneration is difficult because of its cellular and fibrous complexities. Here, we manufactured four different types of PDL-mimic fibrous scaffolds on a desired single mat. These scaffolds exhibited a structure of PDL matrix and human PDL fibroblasts (PDLFs) cultured on the scaffolds resembling morphological phenotypes present in native PDLF. The scaffold-seeded PDLF exerted prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Innovative efforts have been directed at designing fibrous scaffolds that mimic the structure of the periodontal ligament (PDL) matrix, along with the integration of human PDL fibroblasts (PDLFs). These scaffolds, cultured with PDLFs, mirror the morphological traits observed in native PDLFs and evoke proliferative, osteoblastic, and osteoclastogenic potentials based on fiber topographical cues [133,134].…”
Section: Periodontium Regenerationmentioning
confidence: 85%
“…Innovative efforts have been directed at designing fibrous scaffolds that mimic the structure of the periodontal ligament (PDL) matrix, along with the integration of human PDL fibroblasts (PDLFs). These scaffolds, cultured with PDLFs, mirror the morphological traits observed in native PDLFs and evoke proliferative, osteoblastic, and osteoclastogenic potentials based on fiber topographical cues [133,134].…”
Section: Periodontium Regenerationmentioning
confidence: 85%
“…In periodontal tissue, PDLFs attach cement to neighboring alveolar bones, and fibrous connective tissue is involved in this process; 100s of collagen fibers, such as Sharpey's and oxytalan fibers, are included [36]. PDLFs react sensitively to mechanical stimulation through interaction with the fiber-formed matrix [37][38][39]. In this study, HGFs, which were used as a control, reacted to mechanical stimulation, but the reactivities to weights for the production of RANKL and IL-6 were weaker than those of PDLFs.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings have been confirmed in studies on periodontal fibroblasts ( Table 1 ). For example, Kim et al found that YAP not only influenced the morphology and cytoskeleton of PDLFs but it also regulated their proliferation and mineralization through a PDL-mimic fibrous scaffold model ( Kim et al, 2023 ). Moreover, the application of static strain to human PDLFs (hPDLFs) results in significant nuclear translocation of YAP, which is mediated by the activation of extracellular signal regulated kinase (ERK)1/2 ( Hulter-Hassler et al, 2017 ).…”
Section: Yap and Taz Regulate Periodontal Homeostasis And Remodelingmentioning
confidence: 99%